La función pragmática de los anglicismos: Algunos ejemplos en el habla juvenil de las Palmas de Gran Canaria - Mª Isabel González Cruz; Mª Jesús Rodríguez Medina (Miscelánea: A Journal of English and American Studies, 2012)
Anglicisms constitute a complex phenomenon resulting from language contact and the increasing cultural globalization. They are greatly encouraged by the technological and cultural influence exerted by the Anglo-Saxon world. Little has been said so far about usage as a factor. Besides, there is a type of Anglicism of a pragmatic nature which remains almost unexplored. They are used in some communicative situations with a sort of expressive or aesthetic function, which some authors have called ludic or emphathic since they tend to mark oral discourse with humorous or ironic features. In this article we will approach the concept of pragmatic function within this field of anglicisms. To illustrate it, we will provide some examples taken from research previously carried out in the city of Las Palmas de Gran Canaria (Spain) with a group of youngsters, undoubtedly the social group most overtly exposed to the influence of anglicisms.
Keywords: anglicisms; usage; youngters speech; Canarian Spanish; society and culture